Optimalisasi Pengelolaan Bank Sampah Berbasis Pelatihan dan Sosialisasi Pengabdian kepada Masyarakat Berkelanjutan - Mulyana, Eka; Saputra, Ardi; Mardhotillah, Reno (JPM: Jurnal Pengabdian Masyarakat, 2026)
Waste management remains a critical issue in Indonesia, driven by rapid population growth and the increasing volume of household waste that has not been properly addressed. In Meranjat II Village, Indralaya Selatan Subdistrict, Ogan Ilir Regency, waste is still predominantly managed through conventional practices such as open burning or direct disposal into rivers and fields, which contributes to environmental pollution and health risks. To address this challenge, a community service program was introduced to enhance residents’ knowledge and awareness by implementing waste banks as an environmentally friendly and economically beneficial solution. The program engaged residents in socialization sessions, group discussions, and practical waste-sorting activities. Data were collected through observation, interviews, and questionnaires, and analyzed using a descriptive quantitative approach to assess community acceptance. The results revealed significant improvements, with 80% of participants understanding the importance of waste separation, 90% demonstrating greater concern for environmental cleanliness, and 74% expressing willingness to participate in the waste bank program actively. Nevertheless, challenges remain, including limited supporting facilities, low environmental literacy, and uneven participation. Continuous support from village authorities and other stakeholders is essential to ensure the program’s success and sustainability. Overall, this initiative not only raised environmental awareness but also created opportunities for community-based economic empowerment through sustainable waste management.